2014
DOI: 10.1007/s11414-014-9451-6
|View full text |Cite
|
Sign up to set email alerts
|

Better Futures: a Randomized Field Test of a Model for Supporting Young People in Foster Care with Mental Health Challenges to Participate in Higher Education

Abstract: The purpose of the study was to conduct a preliminary efficacy evaluation of the Better Futures model, which is focused on improving the postsecondary preparation and participation of youth in foster care with mental health challenges. Sixty-seven youth were randomized to either a control group that received typical services or an intervention group, which involved participation in a Summer Institute, individual peer coaching, and mentoring workshops. Findings indicate significant gains for the intervention gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…This model is augmented by same-age peers who provide vocational mentorship. The Better Futures Program coordinates care through individualized coaching, peer support, and connection to community resources to support postsecondary education among transition age youth with mental health conditions in foster care (Geenen et al, 2015). Evaluations of these programs are underway.…”
Section: Domain-specific Servicesmentioning
confidence: 99%
“…This model is augmented by same-age peers who provide vocational mentorship. The Better Futures Program coordinates care through individualized coaching, peer support, and connection to community resources to support postsecondary education among transition age youth with mental health conditions in foster care (Geenen et al, 2015). Evaluations of these programs are underway.…”
Section: Domain-specific Servicesmentioning
confidence: 99%
“…Social conditions that meet an individual’s innate psychological needs for autonomy, competence, and relatedness are believed to be essential for driving self-motivation and fostering overall well-being. Based on this theory and a similar utilization of it in another study (Geenen et al, 2015), we anticipate that participation in FHE will help students gain self-determination skills and believe in their ability to be successful in college.…”
Section: Intervention Development Background and Overviewmentioning
confidence: 90%
“…For foster youth with serious mental health challenges who have not yet completed the postsecondary application or enrollment process, the Better Futures near-peer coaching/mentoring program (Geenen et al, 2015; Phillips et al, 2015) has been found to improve students’ postsecondary preparation and access outcomes. It uses an adaptation of the Take Charge model, a self-determination intervention developed for high-risk youth to improve student engagement (Geenen et al, 2015; Powers et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It uses an adaptation of the Take Charge model, a self-determination intervention developed for high-risk youth to improve student engagement (Geenen et al, 2015; Powers et al, 2001). Students enrolled in Better Futures receive support through one-on-one near-peer coaching, mentoring workshops, and by connecting with experienced alumni of foster care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation